PENERAPAN USAHA BELA NEGARA PADA PROFIL PELAJAR PANCASILA DI SD NEGERI 5 KARANGJATI - Haryani, Tri (Sekolah Tinggi Agama Islam Muhammadiyah Blora, 2024)
Students' practice in living the values of the Pancasila precepts has decreased. This is evidenced by the rampant deviant incidents such as fights in public, bullying, harassment, and vandalism. This study aims to analyze the profile of Pancasila students who struggle to defend the country in grade V of elementary school. This type of research is descriptive research. The sample was determined using the cluster sampling technique with a sample of 79 people. The non-test method in the form of a questionnaire will be used for data collection. Two techniques are used during the data analysis stage: quantitative descriptive analysis and qualitative descriptive analysis. The results of the survey data analysis showed that the percentage of students who implemented the Pancasila student profile varied in six dimensions. Each aspect is explained as follows. The first dimension has a score of 86.42% for Faith, Dedication to God Almighty, and Noble Morals, the second dimension has a score of 84.3% for Global Diversity, and the third dimension has a score for Collaboration. 82.08%, the fourth dimension of Independence with a score of 80.38%, the fifth dimension of Critical Thinking with a score of 77.94%, and the sixth dimension of Creative with a score of 80.22%. Therefore, even though the implementation of the Pancasila Student Profile by students can be considered good, there are still some students who give a negative response to the statement. It is hoped that the implications of this research can be explored more deeply, complement and become a starting point for other researchers. Keywords : National Defense, Pancasila Student Profile, Students, Education